ANALYSIS OF QUALITY COST CONTROL IN UD. PROSPEROUS HOPE IN SIDENRENG RAPPANG DISTRICT - rahman, usman; Salida, Amrisal; Suriadi, Suriadi (Universitas Ichsan Sidenreng Rappang, 2022)
This study aims to determine the amount of Quality Cost Control at UD. Prosperous Hope in Sidrap District. The data analysis method used in this research is descriptive, that is, a method that describes or describes the results of the research through disclosure in the form of narratives, graphics or images. Based on the results of the study showed that the internal failure cost reduction at UD. Harapan Makmur can be achieved by adding prevention costs